The early life history of Chiromantes ortmanni (Crosnier, 1965) (Decapoda: Brachyura: Sesarmidae): morphology of larval and juvenile stages - Guerao, Guillermo; Anger, Klaus; Simoni, Riccardo; Cannicci, Stefano (Zootaxa, 2012)
The early life history of the sesarmid crab Chiromantes ortmanni (Crosnier, 1965) was studied at constant laboratoryconditions, and the complete larval and early juvenile development are described. Chiromantes ortmanni showsintraspecific variability in the pattern of larval development, which typically includes 5 or, less frequently, 6 zoeal stagespreceding the megalopa. The regular pathway (with 5 zoeal stages) required ca 18–20 days. During this time span, zoealsize (carapace length) increased by a factor of 2.2 from 0.33 to 0.73 mm, while biomass (measured as zoeal dry mass andcontents of carbon, nitrogen and hydrogen) showed an 8-fold increment. The megalopa moulted after 10–12 days to thefirst juvenile crab stage, the total larval development from hatching to metamorphosis taking approximately one month(or ca. 4 days longer in larvae passing through an additional zoeal stage). First egg-laying was observed 8.5 months later,at a female carapace width of 14.4 mm. After an embryonic development time of 26–27 days, a total of 3,470 larvaehatched during two subsequent nights. Hence, the minimum generation time (from hatching to first offspring release)comprised slightly more than 10 months. Unlike the regular zoeal stages, the supernumerary stage VI showed atypicalcharacters for Sesarmidae larvae, especially in the setation pattern of the first maxilliped and the segmentation of theendopod of the second maxilliped. Some characteristics presented an intermediate morphology between that of the zoeaV and the megalopa. The first juvenile stage (crab I) is described in detail, while only the most relevant morphologicalchanges and sexual differentiation are highlighted for subsequent crab stages (II–IX). Males and females can bedistinguished from instar V onward, based on sexual dimorphism in the pleopods and the presence of gonopores in thefemales. The morphological characters of all larval stages and of the first juvenile crab are compared with those of other Chiromantes spp.